Value of nuclear cardiology for the diagnosis and risk stratification of coronary artery disease - Libhaber, Carlos D.; Vangu, M.D.T.W.H. (SA Heart Journal, 2017)
Nuclear cardiology has developed into an extremely valuable tool for the diagnosis and prognostication of coronary artery disease. With the low sensitivity and specifi city of clinical symptoms, baseline and stress ECG, physicians and cardiologists require noninvasive techniques to detect and risk stratify patients with ischemic heart disease. Myocardial perfusion imaging (MPI) achieves great accuracy in the diagnosis of the disease and in identifying the patients with higher risk for adverse events. Literature shows that it is not the coronary anatomy but the ischemic burden that determines prognosis in patients with ischemic heart disease. Patients with normal MPI, independently of age, gender, symptoms, history of coronary artery disease, presence of anatomic coronary artery disease (CAD) or isotope or imaging technique, have a < 1% risk of adverse events (myocardial infarction or cardiac death) for a period of at least 12 months. Left ventricular function, regional wall motion abnormalities as well as myocardial viability can be evaluated with MPI.